Detection of wheat damping off and root rot disease pathogenic fungi and it bio control by pseudomonas fluorescens - Baghdad Science Journal (مجلة بغداد للعلوم)
This study was conducted to determine the fungal cause and bio control of damping off and root rot of wheat plants by using pseudomonas fluorescens under greenhouse and field conditions. Results showed isolation of eight species from the soil and roots to deferent region of Baghdad government. Rhizoctonia solani (Rs) and Fusarium solani (Fs) were the predominant damping off fungus with frequency 60 and 52% respectively. Led the using of bacteria formulations such as crud suspension , pure bacteria filtration and pure living cells in culture medium inhibit all type fungi with rates ranging from 84-96% , 80- 93% and 75-88% respectively. Rs and Fs were more pathogenesis under greenhouse conditions, with incidence of 80 and 68% and disease severity up to 41,20 and 30,20% respectively. The results of test bacterial formulation (dry, liquid and bacterial filtrate ) with seeds, soil and water irrigation showed high effectiveness for all treatments with superiority of the treatment of seeds in reducing the incidence which reached for the three formulation 21-34% compared with the infested control of Fs, Rs which reached 70 and 55%, respectively. Field experiments results showed superiority of seeds bacterization with dry formulation to reduce the disease incidence to 38% compared with the infested control (75%).These results reflected on the increasing of the shoot and rot dry weight and increasing the productivity (63%) compared with the infested control treatment .